MEDICOLEGAL IMPORTANCE OF ORGANOPHOSPHORUS POISONING IN YOUNG ADULTS - Shazia, Salma; Omair Khan Jadoon,; Mahwish Zeb,; Sarwat Abbasi,; Muhammad Atif Khan,; Haroon ur Rashid,; Aftab Alam Khan,; Maimoona Haroon, (Journal of Ayub Medical College Abbottabad, 2024)
Background: Poison is defined as any substance that harms, endangers, or even kills a person irrespective of the quality or quantity. Pakistan is a developing country and farming is the major occupation of most of the population. Due to the easy availability and increased use of pesticides, accidental and suicidal poisoning is very common. The objective of the study is to find out the most common poison used by people in the general population and its frequency in our setup. Methods: Casualty Department of the Ayub Teaching Hospital in Abbottabad, served as the site of this retrospective investigation. Registrations between January 1st and December 31st, 2023, provided the data. All cases with a history of poisoning were included. Using SPSS 22, the data was analyzed. Sample was limited to those who were admitted when they were still alive. Ethical permission was taken from hospital administration. Results: The study revealed that poisoning was more common among females and the most common age group affected was 16-22years. 57.8% (52) cases were of suicidal intent while 40% (36) were accidental. Conclusion: Female and young people are more prone to Aluminium Phosphide (wheat pill) poison. It is a dangerous and lethal poison, so healthcare workers at emergency department ought to be prepared for such cases. Furthermore, its routine use as a domestic pesticide has to be strictly prohibited by creating awareness among the public. public.